The cost of water in Brussels does not respect the “polluter pays” principle - Xavier May (Brussels Studies)
The water framework order imposes a true cost of water, in line with the “polluter pays” principle. In practice, water consumers in Brussels – both domestic and non-domestic – are the main source of financing for flood control and the collection and treatment of water in the Brussels combined sewer system. However, approximately half of the wastewater is rainwater and extraneous clear water which is not related to water consumption. Consumers should not have to pay for the costs generated by this, in line with the “polluter pays” principle. We estimate that consumers are charged unfairly for 20 % of their water bills. Our research looks into how these amounts could be financed in other ways.